DEVELOPMENT OF RECOMMENDATIONS FOR OPTIMIZATION OF TECHNOLOGICAL PROCESSES OF PROCESSING AND USE OF HEAT AND MASS EXCHANGE EQUIPMENT FOR DRYING LEGUMES - TVERDOHLIB, IHOR; YAROPUD, VITALII; SOLONA, OLENA; POLYEVODA, YURIY; BABYN, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the development of recommendations for the optimization of technological processes of processing and the use of heat and mass exchange equipment for drying legumes. Legumes are an important source of protein and other nutrients in the food and feed industry, and their drying plays a key role in preserving and increasing shelf life. The article includes analysis of technological processes, selection of optimal heat and mass exchange equipment, control of temperature and humidity, reduction of losses of useful substances and implementation of a quality monitoring and control system. Optimizing these processes will help increase production efficiency and improve the quality of dried leguminous herbs, contributing to the development of the industry and meeting the demand for valuable products. In this context, our article is devoted to the development of recommendations for the optimization of technological processes of processing and the use of heat and mass exchange equipment for drying legumes. By combining scientific analysis, practical experience and innovative approaches, we set ourselves the task of developing integrated recommendations that will contribute to increasing the efficiency of the drying process, reducing the loss of useful substances and improving the quality of dried legumes. An important aspect of our article is not only the theoretical base and scientific research, but also a practical approach to solving this problem. We hope that the developed recommendations will find practical application in the agro-industrial sector, contributing to the conservation of resources, increasing the quality and competitiveness of products and contributing to the sustainable development of this important industry.